2015
DOI: 10.1080/09168451.2014.993916
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Dalbergia odorifera protects skin keratinocytes against ultraviolet B-induced photoaging by suppressing production of reactive oxygen species

Abstract: (2015) Ethanol extract of Dalbergiaodorifera protects skin keratinocytes against ultraviolet B-induced photoaging by suppressing production of reactive oxygen species, Bioscience, Biotechnology, and Biochemistry, 79:5,[760][761][762][763][764][765][766]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…DOE was prepared according to a previously described method [26]. Briefly, heartwood of D. odorifera was purchased from a Korean medicinal herb store in Seoul in May 2012.…”
Section: Methodsmentioning
confidence: 99%
“…DOE was prepared according to a previously described method [26]. Briefly, heartwood of D. odorifera was purchased from a Korean medicinal herb store in Seoul in May 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing evidence has indicated that ROS is one of the major causes of UVB-stimulated cellular senescence by damaging DNA strands and/or altering DNA bases [ 20 ]. To examine whether NF50E treatment could suppress UVB-induced cellular ROS production, a DCFDA-ROS detection assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Sativanone was reported to be distributed from the Restharrow root [ 35 ] and the heartwood of Dalbergia odorifera and showed several bioactivities including antibacterial activity against Ralstonia solanacearum [ 30 ] and anti-senescent and antioxidant effects [ 36 ]. This compound was also reported to possibly possess yeast α-glucosidase inhibition by using ultra-filtration liquid chromatography/mass spectrometry (UF-LC/MS) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%